PENGARUH LINGKUNGAN KERJA DAN KOMUNIKASI TERHADAP KINERJA MELALUI MOTIVASI KERJA GURU SMP NEGERI NANGA BULIK, DI KOTA PALANGKA RAYA - Lauren Simanjuntak; Yunikewaty Yunikewaty; Meitiana Meitiana; Roby Sambung (Media Bina Ilmiah, 2022)
This research is in the field of HR management, regarding the influence of the work environment and communication on performance through the work motivation of teachers at SMP Negeri Nanga Bulik, Palangka Raya City. The cooperation of all parties is needed to maximize the performance of each work unit in supporting the implementation of programs and activities for the teachers of SMP Negeri Nanga Bulik. In addition to the cooperation of all parties, it also needs to be balanced with the availability of adequate human resources both in terms of education and the competence and professionalism of each teacher. Quantitative research with the number of respondents 89 teachers and analyzed by PLS. The results of the study prove that the effort to achieve the performance of State Junior High School teachers in Nanga Bulik can also be influenced by various factors, including work environment, communication, and motivation. The results showed that the work environment had no significant effect on performance, but motivation did. On the other hand, communication affects performance, either directly or through work motivation. The implications of the research for school leaders by building strong working relationships with teachers by increasing motivation and providing a comfortable work environment to increase comfort and concentration at work so that performance results will be better and support achievement